Tatalaksana Penggunaan Forceps pada Posisi Oksiput Posterior Persisten - Ratu Astuti Dwi Putri; Nicko Pisceski Kusika Saputra (Jurnal Ilmu Kedokteran, 2021)
Maternal health is the health of women during pregnancy, childbirth and the postnatal period. World Health Organization (WHO) record every day in 2017 about 810 women died from preventable causes related to pregnancy and childbirth. Between 2000-2017, the maternal mortality ratio dropped by about 38% worldwide, but 4% of all maternal deaths occur in low and lower middle-income countries. Persistent occiput posterior (OP) is associated with increased rates of maternal and newborn morbidity. Cesarean delivery is higher (3 times greater risk of death) maternal morbidity and mortality than vaginal delivery and also costs more than normal childbirth. Forceps extraction is one of the operative obstetric actions that aims to help childbirth through normal childbirth. This is done for all conditions that threaten the mother and fetus that have indications to undergo childbirth. the use of forceps techniques, will assure successful, safe, and steady performance of forced delivery. Therefore, obstetric forceps should be inherited of skills to the trainee at this time. Therefore, it is reasonable for the standards establishing the proper position for forceps delivery to vary between experienced and inexperienced operators. The first priority is safe and secure implementation of the procedure.